KLASIFIKASI TELUR AYAM DAN TELUR BURUNG PUYUH MENGGUNAKAN METODE CONNECTED COMPONENT ANALYSIS - Ikhwan Ruslianto (STMIK PONTIANAK, 2013)
Abstract : Research to classify different types of eggs on farms results in a computerized still rare. When in fact can be made of a system of apps that can do the grouping of various types of eggs in abundance. A breeder eggs should not do eggs grouping or counting numbers manually, but with the help of computers, grouping the types of eggs and counting the number of eggs to be precise and accurate. This study provides an alternative to perform grouping or classification of different kinds of eggs using connected component analysis method through an object in an image taken from an egg, so it can solve the problems of classification types of eggs using computer applications. The results of tests on 10 data image that connected component analysis method successfully applied to the classification of eggs with black background conditions and obtained results grouping process chicken eggs and quail eggs with a 100% success rate, and counting the number of eggs classification results with 100% accuracy rate Keywords: segmentation, connected component analysis, classification.